Strategy Of Professional Zakat Fundraising In Zakat Management Institutions - Afief El Ashfahany; Wulan Galuh Savitri; Sheila Putri Anggraeni (LPPM ISNJ Bengkalis, 2023)
This study aims to analyze the strategy of professional zakat fundraising to increase Muzakki's trust. The research was conducted at zakat management institutions, namely at LAZ Al-Abidin, LAZISMU UMS, and LAZISMU in Solo. The method used in this research is a qualitative approach. Data collection techniques include in-depth interviews with related parties, documentation and literature. The results of this study indicate that professional zakat at LAZ Al-Abidin, LAZISMU UMS, and LAZISMU Solo has increased yearly. However, there is a problem at LAZ Al-Abidin and LAZISMU, namely the low level of public understanding of professional zakat, while for LAZISMU UMS, it is about regional coverage. The fundraising strategy carried out by LAZ Al-Abidin and LAZISMU UMS in increasing Muzakki's trust by carrying out data transparency, and increasing teamwork abilities, while LAZISMU Solo expanded marketing and created attractive reports. The strategy carried out by each zakat management institution can gain the trust of the Muzakki so that it can increase the receipt of professional zakat. This research has implications for developing the theory of professional zakat regarding fundraising strategy.